The Role of Islamic Financial Institutions in Supporting National Economic Development - Agus Koni; Triana Apriani; Dayat Hidayat; Nurul Lailatul Vitriyah; Selly Silviawati (Lafadz Jaya Publisher, 2026)
Sustainable national economic development requires support from various sectors, including the financial sector. In recent years, Islamic Financial Institutions (IFIs) have grown rapidly and made significant contributions to supporting national economic development. This study aims to analyze the role of Islamic Financial Institutions in supporting national economic development. This study uses a descriptive qualitative approach. Research data were obtained through in-depth interviews with respondents from Islamic financial institutions, the government, and entrepreneurs. The results show that Islamic Financial Institutions play a significant role in supporting national economic development in several ways, namely: increasing financial access for communities underserved by the conventional financial system, providing more innovative and diverse financial product and service development. In conclusion, the Role of Islamic Financial Institutions in Supporting National Economic Development is increasing transparency and accountability in financial management and supporting regional economic development through the development of micro and small-scale finance. Islamic financial institutions play a significant role in supporting national economic development. Therefore, the government and financial institutions need to continue supporting and strengthening the role of Islamic financial institutions in improving the economic welfare of the community.